Effect of Bulls on Birth Rate and Birth Weight by Using Semi-Intensive Bali Cattle Maintenance - Andi Anjar Wawo (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2018)
Thisstudy wastoknowtheeffectoftheBullonconceptionrateandbirthweightofBalicattleraisedwithsemi-intensively.This study usesan entirely randomized design(CRD) with four treatments with unbalancedata.Thesurveyconductedduringathreemonths periodof December2012toFebruary 2013, at theLaboratory ofbeefcattleProduction,FacultyofAnimalScience,Hasanuddin University,Makassar.Materialsofthe studywereasfourbullsofdamsBalicattlewith age from 2.5to4years,12Balicows,and55 calvesbornfrom2005through 2012.Theanimalshousethroughoutthe yearandthey wereexerciseand grazing,approximately 4hoursinthedaytimeuntilafternoon.Inthehouse,the animalswerefed using elephantgrass,additionalfeed(rice brian),salt,andwateradlibitum.Theresultsofthisstudy showedthatconception rateandcalving rate ofBalicattleraisedsemi-intensive ware95.62% and86.25%respectively. The averagebirthweightwas13,06 kg.Itcanbe concluded thatthe conception rateandbirthweightisaffectedby themales,whilethecalvingratenosignificant effectofBull.